Structural and electronic structure evolution of KxFe2−ySe2 from semiconducting phase to superconducting phase. (1st April 2023) - Wang, JiaJun; Zhu, YongZheng; Li, Li; Wang, ManFu; Zheng, Shuang; Cui, Yan; Liu, ShiMin; Zhang, ZhiHua; He, Ming; Song, Bo; Zhao, Mei
Abstract: The structural parameters, magnetic property and electronic structure of K0.875+ a Fe1.5+ b Se2 have been studied by first principles calculations. An increase of K or Fe content leads to the evolution of the magnetic property and electronic structure of K0.875 Fe1.5 Se2 . The introduction of extra K brings a slight rigid shift of the minority states, while the introduction of extra Fe breaks the vacancy order of Fe atoms, forming 1D chains, and causes the Fermi surfaces to display an obvious nesting feature. The K0.875 Fe1.5 Se2 is proven to be a semiconductor with a 61 meV gap, and the evolution from semiconducting phase to superconducting phase is mainly due to the suppression of a rhombus iron vacancy order and antiferromagnetic order with an increase in Fe content.